2021
DOI: 10.1590/1413-7054202145011921
|View full text |Cite
|
Sign up to set email alerts
|

Selection of superior cowpea lines for multi-traits and adaptabilities to the Piauí semi-arid using genotype by yield*trait biplot analysis

Abstract: Cowpea is a great socioeconomically important leguminous plant worldwide. The crop is an excellent source of proteins and minerals, mainly for the poorest populations. It is cultivated in some states of Brazil. The Piauí semi-arid is the most yielding zone in the state. Thus, the selection of superior cowpea genotypes for multi-traits and adaptabilities to this growing area is very important for the small-scale and medium-scale farmers in Piauí. The objective of this study was to select the superior cowpea lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Significant GE interaction also suggests the need for evaluation of cowpea genotypes in multiple environments and seasons to quantify their stability and adaptability before commercial release and recommendation. Previous studies showed that a significant GE interaction has been reported for cowpea protein, Fe, and Zn content (Araújo et al, 2021). However, a study by Gerrano et al (2019) reported nonsignificant GE interaction for protein and Cu in cowpea breeding populations.…”
Section: Discussionmentioning
confidence: 92%
“…Significant GE interaction also suggests the need for evaluation of cowpea genotypes in multiple environments and seasons to quantify their stability and adaptability before commercial release and recommendation. Previous studies showed that a significant GE interaction has been reported for cowpea protein, Fe, and Zn content (Araújo et al, 2021). However, a study by Gerrano et al (2019) reported nonsignificant GE interaction for protein and Cu in cowpea breeding populations.…”
Section: Discussionmentioning
confidence: 92%
“…According to the four regions' diagrams, the two hybrids KSC705 and KSC604 were identified as desirable hybrids in all regions. Various researchers have used polygon diagrams to evaluate the genotypes of different plants, including sunflower (Ansarifard et al, 2020), corn (Shojaei et al, 2021;Szabó et al, 2022;Illés et al, 2022;Mahrokh et al, 2023), and cowpea (Araújo et al, 2021), sweet corn (Mousavi et al, 2024) sorghum (Khazaei et al, 2022).…”
Section: Polygon Diagrammentioning
confidence: 99%
“…], also known as black‐eyed pea, southern pea, and crowder pea, is an example of a crop that can be biofortified. Cowpea consumption can provide considerable amounts of protein (24.1%) (Araújo et al., 2021; Dakora & Belane, 2019), vitamins (Gonçalves et al., 2016), and micronutrients, such as iron (61.3 mg kg −1 ) and zinc (44.7 mg kg −1 ) (Feitosa et al., 2018). Therefore, biofortification programs are investing in the crop's breeding, aiming at combining grain yield and high nutrient content into the best genotypes.…”
Section: Introductionmentioning
confidence: 99%